Pengaruh pola asuh Orang Tua dan lingkungan pembelajaran terhadap motivasi belajar Siswa di SMAN 103 Jakarta - Yayan hidayatulloh; Rusnita; Ramadhan Putra Astaman; Jelita Ria Hutagalung; Yayan Sudrajat (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2023)
Motivation and learning are two things that influence each other. One of the influencing factors in the learning process is environmental factors, namely parenting, because parenting can influence students in the learning process. The purpose of this study was to examine the correlation between parenting styles and the learning environment with students' learning motivation at SMAN 103 Jakarta. This research was conducted at SMAN 103 Jakarta. The sample consisted of 141 students of SMAN 103 Jakarta. The type of research conducted in this research is quantitative. From these results, the hypothesis which states that there is an influence between parenting and the learning environment simultaneously on students' learning motivation is accepted. There is a significant and positive influence between parenting style on student learning motivation with the coefficient of determination (Adjusted R Square) multiple regression between the independent variables and the dependent variable which is equal to 0.122. This value indicates that the parenting style and learning environment simultaneously contributed 12.2% to student learning motivation and the remaining 87.8% was influenced by other factors on employee performance but were not included in this study. It was concluded that parenting style influences students' learning motivation. It is suggested to parents and schools to be able to apply good parenting, create learning situations that can stimulate students' interest to study hard and pay attention to children's school needs.